Vertebrobasilar Dolichoectasia and Basilar Artery Dissection Presenting With Trigeminal Neuralgia: A Case Report - Wang, Yuhan; Cheng, Wenchao; Lian, Yajun (Frontiers in Neurology, 2019)
Trigeminal neuralgia secondary to vertebrobasilar dolichoectasia and basilar artery dissection is rare. The authors report the case of a 72-year-old man with a 5-year history of right electrical facial pain identical with trigeminal neuralgia. Finally, magnetic resonance imaging and digital subtraction angiography revealed basilar artery dissection and vertebrobasilar dolichoectasia. The patient underwent partial basilar dissecting aneurysm embolization. The facial pain was relieved immediately after the operation and disappeared completely 6 months later. Three years after surgery, the patient had experienced no recurrence of the right facial pain.